Learning Obstacle to Ontogeny of Mathematics Teacher Candidates on Number Theory - Natalia, Stevi; Darhim; Kusumah, Yaya S.; Ditasona, Candra (Journal of Education Reseach and Evaluation, 2023)
Prospective mathematics teachers must have the characteristics of mathematical science, namely systematic, logical, and critical. This study aims to reveal the analysis of learning obstacles experienced by prospective mathematics teachers in number theory lectures with sub-material of division relations, FPB and KPK. This research uses a qualitative approach method in descriptive form. This research was conducted by collecting data through questionnaires and interviews and validated using the triangulation method. The study was limited to the analysis of ontogenic learning obstacles according to Brosseasu. The results of this study were that 4 out of 6 research subjects experienced the occurrence of ontogenic learning obstacles with details of 37.5% of prospective teacher students experiencing psychological ontogenic obstacles and instrumental ontogenic obstacles, then 25% experiencing didactic ontogenic obstacles. This indicates that students' readiness to take part in number theory courses is still weak. Students are weak in terms of psychological readiness, weak in readiness for complete mastery of related material previously studied and weak in terms of following the thought process needed in this course.